Analisis Pendukung Keputusan Penentuan Pembelian Bahan Pokok Untuk Pembuatan Nasi Kotak Menggunakan Fuzzy Tsukamoto - Anam, Achmad Chaierul; Musiri, Ali; Harlinton, Zona; Widyarto, Wahyu Oktri (Journal of Machine Learning and Soft Computing, 2019)
Determining a decision in a business is quite difficult. Various considerations must be carefully calculated. Capital and the number of products ordered are sources of consideration that must be taken into account. This study discusses the implementation of fuzzy tsukamoto in making decisions on purchasing raw materials or making orders for rice boxes, where the input is capital of Rp. 3,500,000 and the number of orders is 500 boxes while the results of this study are four outputs including purchasing 93 Kg of rice, purchasing 47 chicken meat, purchasing 21 vegetables or fresh vegetables and purchasing 37 Kg of citrus fruit.